Ovarian Cancer Revealed by Paraneoplastic Cerebellar Degeneration Anti-Yo Positive: A Case Report - Erraichi, Hayat; Niaina Ezra Randriamanovontsoa; Valère Litique; Jean-Marc Limacher; S. Berrad; Karima Oualla; Lamiae Ammadour; Zineb Benbrahim; S. Arifi; Nawfal Mellas (International Journal of Innovative Research in Medical Science, 2020)
Neurological paraneoplastic syndromes are rare, often associated with gynecological cancer or small cell lung cancer. This article reports a case of ovarian cancer to discuss the difficulties in the management of neurological paraneoplastic syndromes. This is a case of paraneoplastic cerebellar syndrome with anti-Yo antibodies. Neurological syndromes, testing for onconeural antibodies and testing for underlying cancer provide a basis for the diagnosis. The anti-tumor treatment constitutes the mainstay of the care.